Electron Beam Melting of Ti-48Al-2Nb-0.7Cr-0.3Si: Feasibility investigation. (June 2016) - Baudana, Giorgio; Biamino, Sara; Klöden, Burghardt; Kirchner, Alexander; Weißgärber, Thomas; Kieback, Bernd; Pavese, Matteo; Ugues, Daniele; Fino, Paolo; Badini, Claudio
Abstract: In this work, carried out within the European project TIALCHARGER, TiAl-based powders of Ti-48Al-2Nb-0.7Cr-0.3Si, were used to fabricate specimens and prototypes of hollow turbocharger turbines by Electron Beam Melting (EBM). This additive manufacturing technology uses an electron beam to generate parts by selectively melting the powders layer by layer according to CAD data. Components produced with these powders were characterized in terms of residual defects and resulted appropriate both in terms of overall residual porosity and maximum defect size. Furthermore the microstructure of the as produced material was investigated and heat treatments were set up in order to obtain the desired microstructure. This is an essential point for these materials because their mechanical properties are extremely sensitive to microstructure. Chemical composition of powders and massive materials were analysed. Loss of Al was observed, while the levels of impurities were very low and similar for both the powder and the part. Mechanical tests were performed on the heat treated samples and the results are in well agreement with literature data for this TiAl alloy for the desired automotive application. Graphical abstract: Highlights: The processability of the Ti-48Al-2Nb-0.7Cr-0.3Si titanium aluminide alloy was assessed. The EBM process parameters were optimized: cylindrical specimens and turbocharger wheel prototypes were produced. With the proper heat treatment, the desired microstructure in relation with the application was obtained. Promising preliminary mechanical test results.